Evaluation and optimization of the performance of frame geometries for lithium-ion battery application by computer simulation - Miranda, D. (2018)
Tailoring battery geometries is essential for many applications as geometry influences the delivered capacity value. Two geometries frame and conventional have been studied and for a given scan rate of 330C the square frame shows a capacity value of 305,52 Ahm−2 which is 527 times higher than the one for the conventional geometry for a constant the area of all components.